PREPARATION AND PHYSICO-CHEMICAL CHARACTERIZATION OF CARVEDILOL- POLY (LACTIDE-CO-GLYCOLIC ACID) LOADED NANOPARTICLES.: Pharmaceutical Sciences-Pharmacy - PAL, SOVAN LAL; KUMAR MANNA, PRABAL; PRASAD MOHANTA, GURU (International Journal of Life Science and Pharma Research, 2018)
Carvedilol is a non-cardio selectivity β- blocker which is used for the treatment of essential hypertension and symptomatic heart failure. The objective of the present study was to prepare and determine the physicochemical characteristics of Carvedilol-Poly (Lactide-co-Glycolic acid) nanoparticles. The nanoparticles of Carvedilol with Poly (Lactide-co-Glycolic acid) were formulated following the solvent evaporation technique. The impact of various process parameters i.e. drug/polymer ratio, aqueous phase volume and speed of sonication time were evaluated and optimal conditions were established. The physicochemical characteristics of nanoparticles were studied applying Particle Size Analysis, Fourier Transform Infra Red Spectroscopy, Differential Scanning Calorimetry, Scanning Electron Microscopy and Atomic force microscopy. The release rate of carvedilol from various drug/polymer nanoparticles was observed as well. All the prepared formulation using Poly (Lactide-co-Glycolic acid) resulted in nano-range size particles (253-438nm) as detected by Zeta Sizer. The entrapment efficiencies were observed for all the nanoparticles in a range of 65.45 % to 85.56%.The nanoparticles of carvedilol- Poly (Lactide-co-Glycolic acid) observed no chemical interaction between drug and polymer molecules. The Scanning Electron Microscopy image revealed that particles were smooth, spherical in shape. The particle aggregation of the particles was observed by Atomic Force Microscopy study. The nanoparticles exhibited the slower release of drug in comparison with the intact drug and polymer molecules. The method was successfully applied in drug release studies from nanoparticles. The drug release kinetics was found to be fitted into the Higuchi model. According to the finding, formulation of carvedilol- Poly (Lactide-co-Glycolic acid) was able to improve physicochemical characteristics of the drug and possibly will enhance the antihypertensive effects of the drug following its oral administration.